The Determination of Effective Educational Institution at Undergraduate Program of North Sumatra State Islamic University - Tien Rafida (Jurnal Ilmiah Peuradeun, 2017)
Higher Education is an effective educational institution in determining and producing the next scientific generation in the future. There are some factors that can transform the higher education institutions, such as: commitment owned by the organizers, trust, interpersonal communication, leadership and organizational culture. This research was conducted from October 2015 until October 2016. The sample for this research is all lecturers in UIN North Sumatera amounted to 419 lecturers spread across 38 departments under eight faculties. This research aims to analyze the influence of one variable on other variables, either direct influence of 0.241, 0.273 and 0.212 or indirect influence of 0.097, 0.219, 0.120 and 0.472, those are: (culture of undergraduate school (X1), leadership (X2), and interpersonal communication (X3) and exogenous variables are trust (X4), commitment (X5) and effectiveness of undergraduate school (X6). This research use analysis technique of PATH ANALYSYS. Regarding the development model of an effective undergraduate school, it can also be assessed based on system approach techniques, ranging from inputs (to school effectiveness study); Processes/ throughputs; Outputs (of school effectiveness study); and outcomes (longer-term results of study).